Design and simulation of a novel E-mode GaN MIS-HEMT based on a cascode connection for suppression of electric field under gate and improvement of reliability *Project supported by the Key Technologies Support Program of Jiangsu Province (No. BE2013002-2) and the National Key Scientific Instrument and Equipment Development Projects of China (No. 2013YQ470767). (July 2017) - Li, Weiyi; Zhang, Zhili; Fu, Kai; Yu, Guohao; Zhang, Xiaodong; Sun, Shichuang; Song, Liang; Hao, Ronghui; Fan, Yaming; Cai, Yong; Zhang, Baoshun
Abstract: We proposed a novel AlGaN/GaN enhancement-mode (E-mode) high electron mobility transistor (HEMT) with a dual-gate structure and carried out the detailed numerical simulation of device operation using Silvaco Atlas. The dual-gate device is based on a cascode connection of an E-mode and a D-mode gate. The simulation results show that electric field under the gate is decreased by more than 70% compared to that of the conventional E-mode MIS-HEMTs (from 2.83 MV/cm decreased to 0.83 MV/cm). Thus, with the discussion of ionized trap density, the proposed dual-gate structure can highly improve electric field-related reliability, such as, threshold voltage stability. In addition, compared with HEMT with field plate structure, the proposed structure exhibits a simplified fabrication process and a more effective suppression of high electric field.